The Analysis of Learning Process of Formal Junior High School Education and Non Formal Paket B Education at Gunungsitoli - Zebua, Ardi Syah Putra; Maru’ao, Nursayani; Harefa, Trisman; Harefa, Afore Tahir (ITScience (Information Technology and Science), 2024)
This study aims to determine and describe the learning process in the Paket B education program and the differences between Junior High School and the Paket B education program. This research was conducted at PKBMs that implement the Paket B Program in Gunungsitoli City, consisting of PKBM Ziona, PKBM Pelita Bangsa, PKBM Kreasi, and PKBM Perjuangan. The research method used was a qualitative descriptive approach. Data was collected through observation, interviews, and documentation. The results show that the learning process in Paket B consists of 3 types, namely, Independent, Tutorial, and Face-to-Face, and there are differences in the learning process between SMP and Paket B in Gunungsitoli city, such as the characteristics of students, facilities and resources, learning schedules, teaching methods, and examinations carried out. In addition, there are also similarities between these two institutions, such as the curriculum used, which is the national curriculum, and the diploma issued by the Ministry of Education and Culture, which means that Paket B is recognized and has the exact legality of junior high school. The learning process in junior high school tends to be more structured and formal, while in Paket B, it is more flexible and individualized to suit the students. Efforts are needed to integrate the advantages of each learning system to create a more effective learning environment for all learners in each education unit.